From experiment to the experience: building knowledge and identities in the supervised internship in geography teaching - Girotto, Eduardo Donizeti (Geosaberes; Vol 8 No 15 (2017): May - Aug, 2017)
The article discuss the supervised internship in Geography Teaching at Geography Department of São Paulo University. Therefore, we analyzed the students perceptions expressed in internship report present in the end of process. In this discussion, we seeking understand the possibilities that supervised internship practices bring to students building knowledge and practices that expand your formative process, articulating the academics knowledge with those elaborate during the internship experience.
Keywords: Ensino de Geografia, Estágio, Saberes Docentes.